Prevention of CSF leak from the spinal operation site due to either traumatic or iatrogenic injury to the Dura. - Alhemiary, Hayder (Journal of the Faculty of Medicine Baghdad, 2019)
Background: Cerebrospinal fluid leak is a relatively common problem ranging from 0.5% to 18% with traumatic or incidental injury to the Dura intra-operatively1, 2. Traumatic injury mostly occurs due to mechanical trauma with subsequent thecal sac laceration mainly in the thoracolumbar region. Incidental Dural injury commonly happens in patients undergoing spinal surgery for any reason.Objective: Introduce a maneuver to be used during operations when the patients have either traumatic or iatrogenic injury to the Dura which would prevent CSF leak post-operatively.Method: A case series study conducted in Baghdad, medical city, between June 2014 and March 2018 on 250 patients (45 females and 205 males) who had either traumatic or iatrogenic injury to the Dura. The operative technique introduced by Perry was used as a reference1. The maneuver used in this study to manage CSF leak intra-operatively described here in this study for comparison with other articles.Results: In this study 250 cases out of 2500 spinal surgery cases, were diagnosed intra-operatively to have Dural injury either post-traumatic or incidentally during surgery. Dural injury occurred in 70 electively operated cases either incidentally or in cases of Dural exploration for different spine pathologies, of whom 13 patients (5.2%) had spinal surgery at the same site previously.  Conclusions: Proper identification of intraoperative CSF leak is crucial for prevention of post-operative complications. CSF leakage can be prevented by applying and reinforcing all surgical field layers with watertight sutures.Key words: CSF leak, Spine, Dura, Trauma, Iatrogenic.